On the L-duality of a Finsler space with special (α, β) metric - Brijesh Kumar Tripathi; Manoj Kumar Singh (Journal of Hyperstructures, 2023)
R. Miron initiated the study of L-duality in Lagrange and Finsler spaces in 1987.The concrete L-duals of the Randers met-ric, Kropina metric, Matsumoto metric, exponential metric, as well as a few more unique (α, β)- metrics, are really just an of the re-markable results obtained.The importance of L-duality, however, is basically limited to finding the dual of a few key Finsler functions.In this paper, we find L- Dual of a Finsler space with a special (α, β)- metric F =(α+β)3/α2 , where α is a Riemannian metric and β is a differential one form.